A Study on Iris Localization and Recognition on Mobile Phones. (18th November 2007) - Park Park, Kang Ryoung Kang Ryoung; Park Park, Hyun-Ae Hyun-Ae; Kang Kang, Byung Jun Byung Jun; Lee Lee, Eui Chul Eui Chul; Jeong Jeong, Dae Sik Dae Sik
Abstract : A new iris recognition method for mobile phones based on corneal specular reflections (SRs) is discussed. We present the following three novelties over previous research. First, in case of user with glasses, many noncorneal SRs may happen on the surface of glasses and it is very difficult to detect genuine SR on the cornea. To overcome such problems, we propose a successive on/off dual illuminator scheme to detect genuine SRs on the corneas of users with glasses. Second, to detect SRs robustly, we estimated the size, shape, and brightness of the SRs based on eye, camera, and illuminator models. Third, the detected eye (iris) region was verified again using the AdaBoost eye detector. Experimental results with 400 face images captured from 100 persons with a mobile phone camera showed that the rate of correct iris detection was 99.5% (for images without glasses) and 98.9% (for images with glasses or contact lenses). The consequent accuracy of iris authentication was 0.05% of the EER (equal error rate) based on detected iris images.